Medicine and dogmatism in "Neguijon" by Fernando Iwasaki - Castany Prado, Bernat (2012)
This article examines how in the novel Neguijon of the Peruvian writer Fernando Iwasaki, medicine serves as an epistemological symbol through which a skeptical conception of knowledge is expressed. The basically speculative and even reflexive quality of medicine from the 16th and 17th centuries would be both a metaphor of dogmatism which dominated the Spanish and Hispano-American societies from the Counter-Reformation, as well as the dogmatism that tempts humans at any time and place.